Оптимизация геолого-разведочной системы: учебное пособие - Власюк В. И. Виктор Иванович; Калинин А. Г. Анатолий Георгиевич; Бер А. А. Александр Андреевич; Рябчиков С. Я. Сергей Яковлевич; Прохоров В. В. Валерий Викторович; Шестеров В. П. Виктор Петрович (Томск, Изд-во ТПУ, 2018)
Заглавие с титульного экрана